Compositional Effect and Distance Sensitivity: Examining the Distance Elasticity in China and Indonesia Trade Activities - Putu Mahardika Adi Saputra (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2019)
This paper analyzes the change in distance elasticity of trade using bilateral trade data among China and Indonesia and their main trading partners. The empirical method used in this study derived from the gravity model that considers the effect of distance on trade activities behavior. Two causes of change in the elasticity of trade to distance will be exposed, i.e., the distance sensitivity effect (within industries) and the compositional effect (among industries). Specifically, this study would like to prove whether the distance sensitivity effect is more dominant than the compositional effect in explaining the change in distance elasticity of trade. By using four sub-periods and around two hundred industries involved, the result shows that the increase in the role of distance in trade heavily caused by the escalation of distance sensitivity effect in most industries.